1976
DOI: 10.1037/0022-0663.68.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooperative versus individualized instruction on student prosocial behavior, attitudes toward learning, and achievement.

Abstract: The effects of structuring classroom learning cooperatively and individualistically were compared on student ability to take the affective perspective of others, altruism, attitudes toward classroom life, and achievement. Thirty fifth-grade, white, working-class students matched on previous achievement in language arts were assigned to cooperative and individualized conditions for learning language arts for 45 to 60 minutes a day for a 17-day period. The results indicate that cooperative, compared to individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…Over recent years, programs have cropped up that have shown to successfully teach SEL. These range from partial-year programs, to multiyear programs; however, the most successful programs in this area are programs that incorporate the whole school, and these range from one year to multiple years in length (Johnson & Johnson, 1976).…”
Section: • Focused Time On Task In the Classroommentioning
confidence: 99%
See 4 more Smart Citations
“…Over recent years, programs have cropped up that have shown to successfully teach SEL. These range from partial-year programs, to multiyear programs; however, the most successful programs in this area are programs that incorporate the whole school, and these range from one year to multiple years in length (Johnson & Johnson, 1976).…”
Section: • Focused Time On Task In the Classroommentioning
confidence: 99%
“…Johnson & Johnson (1976), who were conducting novel research in the 1970's, found that cooperative learning, one of the foundational skills of SEL, leads to greater student engagement, higher achievement among students, and more empathy among the student body. They stated, "The way in which teachers structure classroom learning determines the way in which students interact with each other and with the teacher, which in turn affects the cognitive and affective outcomes of instruction" (Johnson & Johnson, 1976. p. 446).…”
Section: • Focused Time On Task In the Classroommentioning
confidence: 99%
See 3 more Smart Citations